Transcriptions, paraphrases and modern arrangements of vocal works by Stanisław Moniuszko: an outline of the issues and methodology of research - Grajter, Małgorzata (Interdisciplinary Studies in Musicology, 2023)
The well-known practice of transcribing the most famous works by outstanding composers, especially for the piano, was one of the most widely used methods of popularising music in the 19th century. One can say that it had a similar function to literary translation – just as different language versions and adaptations prove the popularity of literary masterpieces, the fact that transcriptions (for piano, other instrument, or a different ensemble) were created was evidence of the particular interest of the audience. Apart from the composer himself, transcriptions and paraphrases of vocal works by Moniuszko were made by Henryk Melcer-Szczawiński, Władysław Krogulski, Zygmunt Noskowski, Ignaz Friedman, Maurice Dietrich, and others. Nowadays, the role the piano used to perform in a house has largely been replaced by the recording industry and modern media and access to music is unlimited in most countries. This situation significantly reduces the demand for creating “usable” versions of works by famous composers. So is there room for new arrangements of Moniuszko’s works on the modern music market? Jazz productions by Bogdan Halicki and the latest proposal from Włodek Pawlik prove that the problem of promoting music by this Polish composer remains valid – and as time goes by, there is a growing need to adjust these compositions to the tastes of modern audiences. The aim of this article is to characterise transcriptions and arrangements of vocal works by Stanisław Moniuszko and to show different transformations of the original pieces depending on their functions and potential listeners by analogy with literary translation.